THE ROLE OF FRAMEWORK CONTRACTING ON PROCUREMENT PERFORMANCE OF STATE CORPORATIONS UNDER THE MINISTRY OF ENERGY AND PETROLEUM IN KENYA - Kosgei, Obadiah Kipkoech; Kinoti, Dr. Justus (International Journal of Supply Chain Management, 2018)
Purpose: The purpose of this study was to determine the role of framework contracting on procurement performance of state corporations under the ministry of energy and petroleum of Kenya. Methodology: The study adopted a descriptive design and targeted 456 staff of the ten (10) state corporations under the Ministry of Energy of Kenya. The study employed stratified random sampling technique in coming up with a sample size of 214 respondents by use of Slovin's formula: n=N/ (1+e2) whereas questionnaires were the main data collection instruments. The study used both primary and secondary data whereby both correlation and multiple regressions were employed to determine the relationship between and among the variables. Results: Framework contracting plays a positive role in procurement performance of state corporations under the ministry of energy of Kenya. It was also found that procurement method adopted positively affects procurement. The study further showed that employee competence has an impact on procurement performance and ICT is a vital enabler of procurement performance Unique contribution to theory, practice and policy: State corporations should embrace framework contracting as a procurement method. This will improve the performance of procurement function as it allows for flexibility and cost reduction hence improving responsiveness and service delivery by the state corporations.. Keywords: Procurement method, supplier development, employee competence, ICT, procurement performance